On the surface fluxes characteristics and roughness lengths at Zhongshan station, Antarctica. Issue 8 (3rd August 2019) - Liu, Changwei; Li, Yubin; Yang, Qinghua; Wang, Linlin; Wang, Xianqiao; Li, Shimin; Gao, Zhiqiu
ABSTRACT: Over Antarctica, surface fluxes play an important role in the local atmospheric dynamical processes. To reveal the surface fluxes characteristics and aerodynamic and thermal roughness lengths over Zhongshan station, Antarctica, this paper analyzes the data observed at the station during 3 March 2008 through 15 February 2009. It is found that easterlies dominated this site throughout the whole year, with a maximum (average) speed of 25 (5.6) m s −1 at 3.9 m height, and the annual maximum (minimum) surface temperature reached 291.05 (230.05) K, while the annual maximum (minimum) air-specific humidity was 4.1 (0.05) g/kg at 3.9 m height. The maximum (minimum) values of seasonal mean temperature, humidity, each radiation components, sensible and latent heat flux occurred in summer (winter), while for the seasonal averaged wind speed and τ the minimums (maximums) appeared in summer (autumn). After comparing with a partially linear regression method for aerodynamic roughness length and four previous equations that derive thermal roughness length from surface Reynolds number, constant values of aerodynamic roughness length as 3.6 × 10 −3 m and thermal roughness length as 1.2 × 10 −4 m at this site were validated by using the other three level observations and suggested for future studies.